The University of the Philippines at Los Baos Union List of Serials a conversion of record formats from Statistical Analysis System to MINISIS - Anday, Vilma G. (1985)
The study was conducted on how the Serial records of the University of the Philippines at Los Banos Library in Statistical Analysis System (SAS) format, which remained unused, can be converted into a database file structure, MINISIS, in order that a better file management system can be implemented for immediate use and retrieval. A conversion program in Systems Programming Language (SPL) was written with the use of a conversion table. MINISIS has three different processors for entering records into the database but since the Serial records are already encoded and partially validated, the BATCHIN processor was used which is the most appropriate method of converting the file. Appended are sample records which comprise ten percent of the total agricultural holdings which were used to test and debug the system for any error or system flaw.